Infraorbital approach for retrobulbar orbital neurofibroma: a case report - N., Harshitha; S. M., Azeem Mohiyuddin; C. S., Supreeth; Prasad, K. C.; H. S., Brindha; Kumar, H. Mohan (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2019)
Retrobulbar orbital tumours are rare and treatment is challenging. These tumors include cavernous hemangioma, neurofibroma, A-V malformations, glioma etc. A variety of approaches have been used in resection of these tumours. The various approaches in literature include endoscopic transethmoidal and sphenoidal, lateral orbitotomy, transmaxillary infraorbital, and cranial and sub cranial approaches. Such tumours located inferior to the optic nerve can be reached through infraorbital approach avoiding traction on optic nerve or pressure on globe. We are reporting a retrobulbar orbital neurofibroma in a middle aged lady who presented with unilateral loss of vision, episodic giddiness, severe left sided headache, left orbital pain and epiphora on exposure to sunlight. MRI showed well defined 1.8×1.8×1.7 cm enhancing lobulated solid left intraorbital mass extending along the substance of inferior aspect of left optic nerve with mass effect. With transmaxillary infraorbital endoscope assisted approach, the retrobulbar tumor was exposed and enucleated. Floor of orbit was reconstructed with tensor fascia lata and nasal septal cartilage graft. The patient had uneventful recovery and immediate post operative visual acuity was perception of light and likely to improve further. Histopathology revealed neurofibroma. This case report highlights the advantages of infraorbital approach as it is a simple approach along the suture lines through the orbital floor with the help of endoscopic guidance. It has the advantages of avoiding traction on optic nerve or optic chiasma, no retraction of brain, no communication with cranial cavity, no pressure on globe and easy reconstruction of orbital floor.